Radial electric field driven by vertical neutral beamlet injection under future fusion reactor conditions - Xingyuan Xu; Yingfeng Xu; Xiaodong Zhang; Xiaotao Xiao (Nuclear Fusion)
The fast ions and electrons generated by neutral beam injection (NBI) can induce charge separation, resulting in radial electric fields. Employing beamlet injection of small cross-section may effectively generate radial electric field, and adjusting beamlet parameters allows active control over their distribution. A new NBI injection geometry system has been developed in the NEOE code to explore the potential for vertical beamlets injection in future fusion reactor scenarios. Both high-field side and low-field side beamlet vertical injections can establish radial electric fields. In scenarios dominated by collision effects, the direction of the radial electric field is influenced by the toroidal angle of the beamlet. Adjusting the poloidal angle can alter the location of the electric field shear. Injecting particles into the trapped region using broader banana orbits can establish electric fields within the plasma core. Alternatively, injecting particles into the passing region can yield higher electric fields. Under future reactor conditions, conservative estimates of the electric field shear may even surpass critical velocities, potentially contributing to instability suppression.